The levels of miR-155 in epilepsy patients: a meta-analysis - Yi Wang; Cong Chen; Chengyu Ya; Jiangwei Chen; Bingfang Lu; Jinwen Liu; Qiong Wu; Limei Diao; Huihua Liu (Frontiers in Neurology)
BackgroundNeuroinflammation plays an important role in the development and progression of epilepsy. It can be both a result and a potential cause of those seizures. MiR-155 plays a crucial role in inflammatory responses, and its expression is upregulated under various neuroinflammatory conditions. This study aims to compare the expression levels of miR-155 in the brain tissue or serum of epilepsy patients and healthy controls, assessing the correlation between miR-155 levels and epilepsy.ObjectiveThe meta-analysis evaluates to assess and compare the levels of miR-155 in the brain tissue and serum of epilepsy patients and healthy controls.MethodsThe databases PubMed, Embase, Cochrane Library, CNKI, VIP, and WanFang DATA were searched from inception until Dec 30, 2024 by two researchers. The relative expression level of miR-155 in the tissues or serum was the primary outcome of the search. After extracting data independently, the two researchers used the Cochrane Collaboration’s tool for assessing risk of bias. All data were analyzed using Review Manager (V.5.4.1) statistical software.ResultsThis meta-analysis (nine studies, 394 patients) reveals elevated miR-155 in epilepsy patients vs. controls (SMD = 1.62, p = 0.001), especially in brain tissue. Subgroups confirm consistency across ages/regions. Subgroup analysis revealed no significant differences by country (p = 0.31), age category (p = 0.63) and sample source (p = 0.15), indicating robust consistency of the primary findings. MiR-155 may serve as a neuroinflammatory biomarker in epilepsy.ConclusionCompared to healthy controls, the relative expression level of miR-155 in the brain tissue or serum of epilepsy patients increased.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42024558255.